You are Here: Home >< Maths

# Differential Equations help??? watch

1. Using the substitution y=1/u, show that the general solution to (1/y^2)dy/dx + 1/y = e^(2x) is y=1/(Ae^x - e^(2x)???

What I’ve got so far:
dy/du=-1/u^2
u^2(dy/dx) + u = e^(2x)
-du/dx + u = e^(2x)
-du + u dx = e^(2x) dx
But I’m stuck here because you cannot integrate (u dx).

Many thanks
2. (Original post by Constan4699)
Using the substitution y=1/u, show that the general solution to (1/y^2)dy/dx + 1/y = e^(2x) is y=1/(Ae^x - e^(2x)???

What I’ve got so far:
dy/du=-1/u^2
u^2(dy/dx) + u = e^(2x)
-du/dx + u = e^(2x)
-du + u dx = e^(2x) dx
But I’m stuck here because you cannot integrate (u dx).

Many thanks
It looks as though you have just multiplied by dx which you can't do.
You will need to solve the resulting ODE by using an integrating factor because this equation is not separable.
3. (Original post by Constan4699)
Using the substitution y=1/u, show that the general solution to (1/y^2)dy/dx + 1/y = e^(2x) is y=1/(Ae^x - e^(2x)???

What I’ve got so far:
dy/du=-1/u^2
u^2(dy/dx) + u = e^(2x)
-du/dx + u = e^(2x)
-du + u dx = e^(2x) dx
But I’m stuck here because you cannot integrate (u dx).

Many thanks

Have you covered the use of integrating factors? If so do you see how to apply one here?
4. Do you know how to do first order nonseperable ODEs?

Look at the coefficient of the term to determine the integrating factor.

A little prod,

Spoiler:
Show
does look familiar?
5. No I’ve never seen the use of integrating factors - probably why I’m unable to progress then. Please help?
6. (Original post by Constan4699)
No I’ve never seen the use of integrating factors - probably why I’m unable to progress then. Please help?
Maybe watch a video (KhanAcademy is normally good) on integrating factors before continuing? Probably better than explaining it to you here, on the spot.
7. So from my understanding it seems that the integrating factor is e^(-x) (hope this is correct?). So starting again:

du/dx - u = -e^(2x)
So e^(-x)(du/dx) - ue^(-x) = - e^x
Can anyone give me any pointers from here?
8. (Original post by Constan4699)
So from my understanding it seems that the integrating factor is e^(-x) (hope this is correct?). So starting again:

du/dx - u = -e^(2x)
So e^(-x)(du/dx) - ue^(-x) = - e^x
Can anyone give me any pointers from here?
Recall the product rule,

Also that . (you should also be familiar with the derivative of e^x) Does this help?
9. (Original post by _gcx)
Recall the product rule,

Also that . (you should also be familiar with the derivative of e^x) Does this help?
Yep thank you very much I think I’ve got it now

### Related university courses

TSR Support Team

We have a brilliant team of more than 60 Support Team members looking after discussions on The Student Room, helping to make it a fun, safe and useful place to hang out.

This forum is supported by:
Updated: October 10, 2017
Today on TSR

### Exam Jam 2018

Join thousands of students this half term

Poll
Useful resources

### Maths Forum posting guidelines

Not sure where to post? Read the updated guidelines here

### How to use LaTex

Writing equations the easy way

### Study habits of A* students

Top tips from students who have already aced their exams